Effects of sex, age, and body mass index on serum bicarbonate - Duan, Daisy; Perin, Jamie; Osman, Adam; Sgambati, Francis; Kim, Lenise J.; Pham, Luu V.; Polotsky, Vsevolod Y.; Jun, Jonathan C. (Frontiers in Sleep, 2023)
Rationale: Obesity hypoventilation syndrome (OHS) is often under-diagnosed, with significant morbidity and mortality. Bicarbonate, as a surrogate of arterial carbon dioxide, has been proposed as a screening tool for OHS. Understanding predictors of bicarbonate could provide insights into risk factors for OHS. We hypothesized that bicarbonate levels increase with BMI, since the prevalence of OHS increases with BMI. Methods: We used the TriNetX Research Network, an electronic health record database with de-identified clinical data from participating healthcare organizations across the U.S., to identify 93,320 adults without pulmonary or advanced renal diseases who had serum bicarbonate and BMI measurements within 6 months of each other between 2017-2022. We used linear regression to examine the associations between bicarbonate and BMI, age, and their interactions for the entire cohort and stratified by sex. We also applied a non-linear machine learning algorithm (XGBoost) to examine the relative importance of age, BMI, sex, race/ethnicity, and obstructive sleep apnea (OSA) status on bicarbonate. Results: This cohort was 56% female, 72% White, 80% non-Hispanic, with an average (SD) age of 49.4 (17.9) years and an BMI of 29.1 (6.1) kg/m2. Mean bicarbonate was 24.8 (2.8) mmol/L, with higher levels in men (mean 25.2 mmol/L) than in women (mean 24.4 mmol/L). We found a small negative association between bicarbonate and BMI, with an expected change of -0.03 mmol/L in bicarbonate for each 1 kg/m2 increase in BMI (p<0.001), in the entire cohort and in both sexes. We found sex differences in the bicarbonate trajectory with age, with women exhibiting lower bicarbonate values than men until age 50, after which bicarbonate levels were modestly higher. Non-linear machine learning algorithm similarly revealed that age and sex played larger roles in determining bicarbonate than BMI or OSA status. Conclusions: Contrary to our hypothesis, BMI is not associated with elevated bicarbonate levels and age modifies the impact of sex on bicarbonate.